Impasses do trabalho socioeducativo em meio aberto: a responsabilização entre a ação técnica e a ação política - Bertol, Carolina Esmanhoto (2019)
In this paper, we propose an analysis of the practices of the professionals of two services that offer socio educational measures in open environment, to understand how they act towards seeking the responsibility of the adolescents involved in infractions. Because it is a care policy that involves both the Justice System and the Single Social Assistance System, it involves different actions, but with a commom direction of work, formulated by the legal frameworks in force in three dimensions: the disapproval of the act, the social integration through the guarantee of rights and the accountability. By this way, in addition to the tensions already existing in conceptions of socio-education in the legal sphere, it is to be expected that other tensions will appear when we focus on the social work carried out by the professionals of the assistance policy who, when acting in contexts of violations and violence are faced with paradoxes, impasses and contradictions. Thus, if the notion of accountability, given its relative novelty, has been more widely debated (from the paradigm of the subject of rights and especially since the introduction of restorative practices in the juvenile justice system), in the operational plan of social work, especially in the open, this notion demands for more conceptual and methodological attention. Given the specificities of the Brazilian reality, of deep social inequalities and of not sustaining a full citizenship, we seek subsidies in Butler to think of accountability as a process that stems from an interpersonal bond between the subject and the other, and from the theoretical contribution psychoanalytic approach of Freud and Lacan, in order to problematize the possibilities of acting with the aim of being accountable to a social bond that generates the segregation of some. We conducted an intervention research with the social technicians of two services of socio educational measures in open environment, following their work routine and conducting discussions of cases attended. Using the analysis model proposed by Costa-Rosa and Lacan's theory of discourses, we analyze how the two institutions understand the infraction and the work to be carried out, how they are institutionally organized to do it, what links they establish with adolescents, and the effects of their practices. From this analysis, we realize that the work of accountability involves a political dimension, which implies changing the position of the adolescent in the social bond. A process based on a listening that interrogates and moves from the position of object of the norm (adhere or not to join) to that of a subject that is constituted in relation to the norms, allowing him a reflexivity about his position in the bond social and moralities and discourses that cross their constitution in this tie. This process also implies the questioning of the hegemonic discourses and norms, which naturalize the violation of the rights in which they are exposed, producing new narratives for the problems and allowing a production of new places in the social bond. To effective this process, a collective work organization is fundamental, in which professionals actually have autonomy of action, and not only become objects of the norm